Role of Loop Electrosurgical Excision Procedure (LEEP) in the Management of Cervical Intraepithelial Neoplasia (CIN) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Abstract not availableBangladesh J Obstet Gynaecol, 2012; Vol. 27(1) : 1-3